Experimental Study of Motion Modes of Discrete Drum with Different Input (Texas Journal of Engineering and Technology, 2022)
The article presents an analysis of the dynamics of interaction of a single fiber with the sampling drum of a headset during pnevmomechanical spinning. The regularity is investigated and the equation of the movement of fibers on the surface of the tooth of the sampling drum headset is obtained. It was found that the dependences of the movement of fibers along the tooth at different angles of inclination, the distribution of fiber tension along the arc, and the distribution of fiber speeds in the region of the sampling arc have an increase property. As a result of the analysis of the tension and speed of the fibers, it was found that with the increase in the sampling zone, the tension force and speed of the fiber increase.